2015
DOI: 10.4161/2162402x.2014.994446
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 secreting tumor-targeted chimeric antigen receptor T cells eradicate ovarian tumorsin vivo

Abstract: A novel approach for the treatment of ovarian cancer includes immunotherapy with genetically engineered T cells targeted to ovarian cancer cell antigens. Using retroviral transduction, T cells can be created that express an artificial T cell receptor (TCR) termed a chimeric antigen receptor (CAR). We have generated a CAR, 4H11-28z, specific to MUC-16 antigen, which is the over-expressed on a majority of ovarian tumor cells and is the retained portion of MUC-16 after cleavage of CA-125. We previously demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
257
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 357 publications
(271 citation statements)
references
References 39 publications
(58 reference statements)
0
257
1
Order By: Relevance
“…Some studies have revealed the anti-tumor function of CARmodified T cells in vitro and in several animal models. Koneru et al (Koneru et al 2015) have designed the fourth-generation of CAR (4H11-28z/IL-12) against MUC-16 ecto antigen that overexpresses on the surface of ovarian tumor cells and is the residue of MUC-16 after CA-125 cleavage. This study indicates that co-expression of IL-12 and 4H11-28z CAR T cells' increased proliferation and IFN-g secretion when compared with 4H11-28z CAR T cells in the SKOV3 cell line.…”
Section: Clinical Trials With Different Generations Of Car T Cellsmentioning
confidence: 99%
“…Some studies have revealed the anti-tumor function of CARmodified T cells in vitro and in several animal models. Koneru et al (Koneru et al 2015) have designed the fourth-generation of CAR (4H11-28z/IL-12) against MUC-16 ecto antigen that overexpresses on the surface of ovarian tumor cells and is the residue of MUC-16 after CA-125 cleavage. This study indicates that co-expression of IL-12 and 4H11-28z CAR T cells' increased proliferation and IFN-g secretion when compared with 4H11-28z CAR T cells in the SKOV3 cell line.…”
Section: Clinical Trials With Different Generations Of Car T Cellsmentioning
confidence: 99%
“…Secretion of bispecific T cell engagers by activated T cells [27] IL12 production and secretion by chimeric antigen receptor T cells [28] Marker Gene modification allows cell labeling, which can either be tracked in vivo (often using transgenes that aid in imaging) or ex vivo (featuring unique sequences that are seldom normally found in the labeled cells (see recommended review [29])…”
Section: Category Description Examples/referencementioning
confidence: 99%
“…Conversely, other investigators are testing dual constructs requiring both targets to be expressed on tumor cells in order to exert their cytotoxic activity (114) and inhibitory CARs able to redirect T cells activity from healthy tissues (115), with the aim of increasing CAR specificity and of preventing off-tumor side effects. Furthermore, many efforts are being made to optimize co-stimulatory molecules and to improve the structure of CARs (116), and new constructs able to locally deliver immune-modulating cytokines (117)(118)(119)(120), bearing modified cytokine receptors (121) or targeting tumor matrix components (122,123) are being developed to overcome environmental barriers. Some groups are also exploring the possibility of combing CAR T cells with oncolytic viruses (124) or with checkpoint inhibitors (125)(126)(127).…”
Section: Car T Cells For Solid Tumorsmentioning
confidence: 99%